TRACHYPHARYNX CIBODASI SP.N. (STRONGYLOIDEA : CYATHOSTOMIDAE), A NEW STRONGYLID FROM A RAT, RATTUS TIOMANICUS FROM CIBODAS, WEST JAVA, INDONESIA - Endang Purwaningsih; Purnomo Purnomo (BRIN Publishing (Penerbit BRIN), 1992)
Trachypharynx cibodasi sp.n. a new strongylid from a rat, Rattus tiomanicusfrom Cibodas-West Java, lndonesia is described. It differs from other species of Trachypharynx in having less number corona radiata internal elements (20), smaller body measurements and esophageal structure.